Synthesis of carbon-supported Pd–Co bimetallic catalysts templated by Co nanoparticles using the galvanic replacement method for selective hydrogenation. Issue 36 (21st April 2017) - Yoshii, Takeharu; Nakatsuka, Kazuki; Kuwahara, Yasutaka; Mori, Kohsuke; Hiromi Yamashita,
Abstract : Carbon-supported Pd–Co catalysts prepared by galvanic replacement were proven to be active for the selective hydrogenation of phenylacetylene. Abstract : Pd–Co bimetallic catalysts were prepared by the controlled synthesis of carbon-supported Co catalysts, ranging from single-sites to nanoparticles, via structural transformation of a deposited Co(salen) complex precursor by heat treatment at different temperatures, followed by galvanic replacement with Pd ions. The catalysts were structurally characterized using XRD, TEM, HAADF-STEM, XAFS and XPS. Highly dispersed Pd-rich NPs containing a low concentration of Co species were formed and the original size of the Co NPs was retained. The electronic state of the Pd species was dependent on the size of the bimetallic NPs, and a catalyst with a mean diameter of 10.8 nm was found to be in the most electron-rich state. Not only the particle size, but also the electronic state of Pd play a crucial role in attaining high catalytic activity and selectivity in the selective hydrogenation of phenylacetylene. A Pd–Co catalyst based on a Co catalyst heat-treated at 600 °C showed 92% selectivity at 93% conversion. Furthermore, the Pd–Co catalysts synthesized by the galvanic replacement method showed superior performance to a monometallic Pd catalyst and a Pd–Co alloy catalyst.